Mild Phenotype in a Patient with a De Novo 6.3 Mb Distal Deletion at 10q26.2q26.3. (29th July 2015) - Tanteles, George A.; Nikolaou, Elpiniki; Christou, Yiolanda; Alexandrou, Angelos; Evangelidou, Paola; Christophidou-Anastasiadou, Violetta; Sismani, Carolina; Papacostas, Savvas S.
Abstract : We report on a 29-year-old Greek-Cypriot female with a de novo 6.3 Mb distal 10q26.2q26.3 deletion. She had a very mild neurocognitive phenotype with near normal development and intellect. In addition, she had certain distinctive features and postural orthostatic tachycardia. We review the relevant literature and postulate that certain of her features can be diagnostically relevant. This report illustrates the powerful diagnostic ability of array-CGH in the elucidation of relatively mild phenotypes.